2022
DOI: 10.3390/life12081146
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Quercetin in the Management of Type-2 Diabetes Mellitus

Abstract: Diabetes Mellitus (DM) is a metabolic disorder that is spreading alarmingly around the globe. Type-2 DM (T2DM) is characterized by low-grade inflammation and insulin resistance and is closely linked to obesity. T2DM is mainly controlled by lifestyle/dietary changes and oral antidiabetic drugs but requires insulin in severe cases. Many of the drugs that are currently used to treat DM are costly and present adverse side effects. Several cellular, animal, and clinical studies have provided compelling evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 141 publications
0
36
0
2
Order By: Relevance
“…On the other-hand, trigonelline improves the insulin signalling pathway, attenuates the endoplasmic reticulum stress and oxidative stress in type 2 diabetic rats, and affects the regeneration of pancreatic islet β-cells, the secretion of insulin, and glucose metabolizing enzymes, and diosgenin protects the pancreatic islet β-cells and up-regulates the hepatic glucose kinase ( Sun et al, 2020 ). ( Ansari et al, 2022 ). In the present study, quercetin and trigonelline content of IM6E was found to be in higher concentration than diosgenin.…”
Section: Discussionmentioning
confidence: 99%
“…On the other-hand, trigonelline improves the insulin signalling pathway, attenuates the endoplasmic reticulum stress and oxidative stress in type 2 diabetic rats, and affects the regeneration of pancreatic islet β-cells, the secretion of insulin, and glucose metabolizing enzymes, and diosgenin protects the pancreatic islet β-cells and up-regulates the hepatic glucose kinase ( Sun et al, 2020 ). ( Ansari et al, 2022 ). In the present study, quercetin and trigonelline content of IM6E was found to be in higher concentration than diosgenin.…”
Section: Discussionmentioning
confidence: 99%
“…The current antidiabetic drugs are designed to alleviate DM and its associated complications, but they are costly and demonstrate remarkable adverse side effects. Phytoconstituents have traditionally emerged as a treatment for DM, particularly as they are inexpensive and have a good reputation for presenting fewer side effects [ 35 ]. In this context, there is a necessity to explore and develop new natural antidiabetic candidates.…”
Section: Discussionmentioning
confidence: 99%
“…By decreasing caspase-3 proteins and glucotoxicity and lipotoxic effects by reducing Akt and Bcl-2 anti-apoptotic activities, activating signaling pathways guards against apoptosis in cells. In chronic hyperglycemia or hyperlipidemia, Àcell survival is improved by cAMP-mediated signaling [174,175]. As previously noted, kaempferol is a special antidiabetic chemical.…”
Section: The Protective and Therapeutic Role Of Flavonoids Against Di...mentioning
confidence: 92%